Rhetoric Situation of Political Parties in Social Media - Dini Safitri (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
The purpose of this study is to give the reader a description of the situation rhetoric of political parties in social media. To get a description, the researcher uses the situation theory rhetoric of Bitzer, communicative action Habermas, and Toulmin model of argumentation. The results showed rhetoric situation led to the construction of the rhetoric message produced in social media. The rhetoric message was the subject of conversation in social media, which is produced intentionally to persuade others. In order to persuade others, the political parties made a number of claims that political parties have been working for the interests of the people, by using a number of data, such as photos of activities, growth chart, statement, and so forth. Based on the claim, the political parties are trying to influence netcitizens to give voice support to political parties. Thus, an agreement together was made to win the candidate of a particular political party.